1995
DOI: 10.1016/0735-1097(95)00329-0
|View full text |Cite
|
Sign up to set email alerts
|

Independent prognostic value of intravenous dipyridamole with technetium-99m sestamibi tomographic imaging in predicting cardiac events and cardiac-related hospital admissions

Abstract: Patients with normal study results or a small defect after intravenous dipyridamole Tc-99m sestamibi SPECT imaging had an excellent short-term prognosis. Those with abnormal results (reversible or large defect) had an increased risk of subsequent cardiac death, nonfatal myocardial infarction and other cardiac-related hospital admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(35 citation statements)
references
References 29 publications
3
30
1
1
Order By: Relevance
“…We found a rate of primary outcome of 1.71% within one year for the patients with altered scintigraphy, as compared with 6.04% for patients with normal tests. Our results, although they present only a trend towards statistical significance (p=0.086) for the occurrence of primary outcome are in accordance with the literature 19,31,[37][38][39] (Chart 1).…”
Section: Discussionsupporting
confidence: 81%
“…We found a rate of primary outcome of 1.71% within one year for the patients with altered scintigraphy, as compared with 6.04% for patients with normal tests. Our results, although they present only a trend towards statistical significance (p=0.086) for the occurrence of primary outcome are in accordance with the literature 19,31,[37][38][39] (Chart 1).…”
Section: Discussionsupporting
confidence: 81%
“…(32)(33)(34)(35)(36) These reports all confi rmed the benign outcome in patients with a normal MIBI study over this follow-up period. Recently published reports have also demonstrated a good prognosis over even longer follow-up periods.…”
Section: Discussionmentioning
confidence: 62%
“…(5,6) The prognostic signifi cance of a normal stress-redistribution Tl-201 myocardial perfusion study in patients with known or suspected CAD is well documented, showing a benign outcome in such patients over the short-and long-term, with an overall cardiac event rate of less than 1% per year. (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) Previous studies have evaluated the prognostic value of a normal Tc-99m MIBI stress study over a period of 6-16 months using planar imaging, (32) over one year using single photon emission computed tomography (SPECT) or planar imaging, (33) over 19.6 months using dual isotope Tl-201 (rest) and Tc-99m MIBI (exercise) SPECT, (34) after dipyridamole Tc-99m sestamibi imaging (35) and over 22 ± 13 months after dobutamine-atropine stress. (36) All these studies confi rmed a benign short-term outcome in these patients with an overall cardiac event rate of less than 1% per year.…”
Section: Introductionmentioning
confidence: 99%
“…(56) When an MPI is found to be abnormal, the risk for hard events is related to the severity of the abnormality; the greater the affected area, the higher the risk. (51,(57)(58)(59)(60)(61)(62)(63)(64)(65)(66) Hachamovitch et al found that patients with a mildly abnormal scan were at intermediate risk for myocardial infarction (2.7%) but low risk for cardiac death (0.8%). (60) If the patients had to undergo pharmacological testing for any reason, or are elderly, have previous history of CAD, diabetes mellitus or atrial fi brillation, even with a mildly abnormal scan, the risk is increased.…”
Section: Discussionmentioning
confidence: 99%
“…(70,71) Fixed and reversible stress perfusion defects predict hard events; still, patients with extensive stress-induced defects are the ones at higher risk. (57)(58)(59)(60)62,63,65,(71)(72)(73) Perfusion defects are not the only determinants of risk. When MPI is performed with 201-Tl, abnormally increased tracer uptake of the FIGURE 1: Stress-rest MPI studies showing severe apical, apical-anterior, midanterior, mid-anteroseptal and basal-anteroseptal segments, stress induced ischemia (Short axis, vertical long axis and horizontal long axis views.…”
Section: Discussionmentioning
confidence: 99%